Klamidija trahomatis in humana papiloma virusa 16 in 18 pri mladostnicah - Vrtačnik-Bokal, Eda (Zdravniški vestnik, 2003)
Background. Adolescents represent a risk group for sexually transmitted infections. The aim of this study was to find the incidence of Chlamydia trachomatis (CT) and human papillomavirus (HPV) in adolescents. Additionally, we wanted to know, whether the prevalence of CT was so high that antibiotic prophylaxis would be appropriate before termination of pregnancy. Patients andmethods. In the study 200 adolescents aged 15 to 19 years were enrolled: 100 came for termination of pregnancy and 100 for a contraceptive method. In all cases the cervical smears were taken for culture and direct immunofluorescence (DIF) for CT. The cervical smear was used also for hybridiyation test for the detection of HPV 16 and HPV 18. Serologic analysis for hepatitis B, HIV and syphilis were done in all cases. Results. CT was isolated in 6% in the first and in 4% in the second group Using DIF method CT was confirmed in 7% in the first and in 4% in the second group. HPV 16 or 18 was positive in 26% in the first and in 13% in the second group. We did not find any case of syphilis, HIV and hepatitis. Conclusions. A 6% prevalence of CT justifies the use of antibiotic prophylaxis before termination of pregnancy.
Keywords: Abortion, Legal; Abortus legalni; Adolescenca; Adolescence; bacteria; bakterije; Chlamydia Trachomatis; Contraceptives, Oral, Hormonal; ginekologija; infekcije; klamidija; Kontracipiensi oralni, hormonski; mladostnice; Papillomavirus, Human; papiloma virusi; Papilomavirus človeški; Sex Behavior; Sexually Transmitted Diseases; Spolno prenosljive bolezni; Spolno vedenje; Vaginal Smears; Vaginalni razmazi